When the worm has a longing (Palíndromo, 2019)
This artistic report focuses on the series As a child, the worm dreamed of being..., created by the artist Elke Coelho in 2012 and 2013. The work in question promotes the convergence between two collections, one composed by objects and another by words. The relation between the realms of objects and language is established through structural, sensorial and/or metaphorical analogies in the field of Contemporary Art.
Keywords: object; collection; analogy; contemporary art